Vertebral osteomyelitis presenting with pleuritic chest pain and bilateral pleural effusions. Issue 5 (May 1992) - Sullivan, P J; Currie, D; Collins, J V; Johnstone, D J; Morgan, A
Abstract : Pyogenic non-tuberculous vertebral osteomyelitis presented with pleuritic chest pain and basal shadowing on the chest radiograph.